Functional outcome in the middle course of bipolar disorder: A longitudinal study - Martino, Diego Javier (2017)
The aim of this study was to assess the long-term functional outcome of patientswith bipolar disorder (BD). At baseline and after a follow-up period of at least 48 months, three measures of functioning were administered: psychosocial functioning (GAF), employment status (full-time, part-time, and unemployment/ disability), and a self-reported measure of functional recovery. At baseline, patients with more than five previous affective episodes exhibited poorer outcomes on all measures of functioning than patients with less than five previous episodes. However, along a mean follow-up period of 77 months, measures of functioning tended to remain stable or improved slightly. These results highlight the limitation of studies comparing measures of functioning between patients with many and few episodes to evaluate functional outcome. Likewise, these preliminary results do not support the hypothesis that functional outcome deteriorates over the course of BD.